(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Background: In the modern competitive world, cardiovascular challenges are becoming common and becoming responsible for early deaths. Myocardial Infarction (MI) is a predominant cause of pre-mature deaths. Numerous Procedures have been applied to evaluate MI risk. For the evaluation of MI risk, a separately developed MIRAT is employed. Even though significant strides have been achieved to reduce mortality, coronary artery disorders (CAD) remain the leading cause of death in many nations, making it one of the major health issues facing the world. Therefore, one of the most crucial health concerns in many nations, including Iran, may be the need to investigate risk and effective factors for CAD. Objective: To evaluate the threat of Myocardial infarction among people in the middle age population using the MIRAT Method: This is a prospective interventional study carried out over a length of 24 weeks after obtaining the institutional Human Committee approval. MIRAT was used in this research which includes 16 self-reporting questions covering age, gender, diabetic history, smoking history, records of hypertension, and family records of coronary heart assault prior 55 years of age etc., This information helps to evaluate the hazard of Myocardial infraction based on danger score criteria. In case the resulting points are greater than 10, considered patients are at greater threat of getting MI. Results: Using the inclusion criteria, 100 subjects were involved in the research. 36 of them were women, while 64 of them were men. The ages 35 to 50 made up the bulk of the population, while 23% of people were from an agricultural background and 38% were from the business sector. Twenty-two (22%) of the 100 participants were found to possess a greater threat of developing MI. Conclusion: The study’s findings showed that the MIRAT can be used to foretell the possibility of time ahead of Myocardial infarction.